Соціолінгвістичні характеристики дискурсу фітнес-класу - Білоус, І. М.; Bilous, I. M. (Волинський національний університет імені Лесі Українки, 2012)
Статтю присвячено розгляду конститувних ознак дискурсу фітнес-класу. Автор характеризує умови та особливості перебігу мовленнєвої взаємодії на фітнес-заняттях. The article deals with the analysis of the constitutive elements of fitness-class discourse. The author makes an attempt to give the overall characteristic of conditions and peculiarities under which the communicative interaction in a fitness-class takes place.
Sociolinguistic Characteristics of Fitness-Class Discourse
Keywords: дискурс; discourse; інтертекстуальність; intertextuality; концепт; concept